1962
DOI: 10.1063/1.1732360
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer Spectra of Some Iron Complexes

Abstract: Mössbauer spectra were obtained for the following coordination compounds: iron phthalocyanine, ferrocene, iron carbonyl, iron III acetylacetonate, and iron II acetylacetonate dipyridine; for the following complex ion salts iron II trisphenanthroline chloride, iron III EDTA (monosodium salt), iron II EDTA, hemin, ferricium picrate, sodium nitroprusside, and some ferro- and ferricyanides. The isomer shift (relative to stainless steel) for iron II has the value expected for an inorganic ion only fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1967
1967
2004
2004

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(13 citation statements)
references
References 8 publications
2
11
0
Order By: Relevance
“…The blue precipitate, once recovered, isolated, and dried, gave an IR spectrum coincident with that of a sample of Prussian Blue obtained by mixing ferrocyanide and ferric ions, and also with that of a sample of Turnbull Blue obtained by mixing ferricyanide and ferrous ions; it is well known that both species are the same, ferric ferrocyanide, since ferricyanide oxidizes ~e ' + to ~e~+ , being itself reduced to ferrocyanide (45)(46)(47)(48). There exist, in fact, two different types of Prussian Blue: (a) soluble Prussian Blue, Fe1'1M+Fe11(CN)6, which is formed when the alkaline ion M+ is in excess, and (b) insoluble Prussian Blue, Fe4[Fe(CN)6]3, when the alkaline and ferric ions are present in similar amounts (49, 50); the IR spectra of both species are identical.…”
Section: Generalmentioning
confidence: 66%
“…The blue precipitate, once recovered, isolated, and dried, gave an IR spectrum coincident with that of a sample of Prussian Blue obtained by mixing ferrocyanide and ferric ions, and also with that of a sample of Turnbull Blue obtained by mixing ferricyanide and ferrous ions; it is well known that both species are the same, ferric ferrocyanide, since ferricyanide oxidizes ~e ' + to ~e~+ , being itself reduced to ferrocyanide (45)(46)(47)(48). There exist, in fact, two different types of Prussian Blue: (a) soluble Prussian Blue, Fe1'1M+Fe11(CN)6, which is formed when the alkaline ion M+ is in excess, and (b) insoluble Prussian Blue, Fe4[Fe(CN)6]3, when the alkaline and ferric ions are present in similar amounts (49, 50); the IR spectra of both species are identical.…”
Section: Generalmentioning
confidence: 66%
“…The X-ray structure of [Fe(acetylacetonato) 3 ] has been known for almost 50 years and consists of an Fe(III) ion in a fairly regular octahedral environment of oxygen atoms with Fe-O=1.95 [88]. For the unsubstituted complex and for various complexes in which the ligand is substituted at the 2position (X=Cl, Br, I, CH 3 , C 6 H 5 , NO 2 ) 57 Fe Mössbauer spectra and the magnetism indicate that they are purely high spin [89][90][91][92]. However, for the complex derived from 4,4,4-trifluoro-1-(3-pyridyl)-1,3-butane-dione the temperature dependence of the magnetic moment (3.69 B.M.…”
Section: Tris(monothio-b-diketonato)iron(iii) Compoundsmentioning
confidence: 99%
“…The metallocarboranes have been discussed in recent review^,^^^^" and the synthesisJ7 and structure3* of a sulfur analogue have been reported. The Mossbauer spectral data for several of these compounds are given in TABLE 4 and FIGURES 2, 3 and 4. Note that the isomer shifts are reduced from the ferrocenevalue and that the residual quadrupole splittings for the iron(II1) systems are larger than the analogous t .…”
mentioning
confidence: 99%